Pengaruh Peer Instruksi Flipped terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas XI SMAN - Octariani, Dhia; Madayani, Agustin; Sembiring, Metrilitra Br (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
In the educational process, it will be found that mathematics learning will be learned from the early education level, the average student has difficulties in solving mathematical problems, especially the ability to solve mathematical problems that affect students' answers, starting from understanding the problem, the problem-solving process, and rechecking whether the answer is correct or not, students are still relatively low. Many factors can affect low problem-solving skills such as monotonous learning and conventional learning. This study aims to find out how much influence the peer instruction flipped learning model has on mathematical problem-solving skills. The type of research used is quantitative research with a quasi-experimental method. The population in this study is 296 students and a sample of 66 students. Data collection was carried out using SPSS 29 and a problem-solving ability test in the form of an essay (description) which was compiled according to the problem-solving ability indicator according to polya. The results of the study, namely in the N-Gain test, there was an influence of the flipped peer instruction learning model on the mathematical problem-solving ability of students in the experimental class by obtaining an increase of 47.80 or 48% in the medium category. In the results of the Difference test (T-Test), it can be seen from the value of Sig. (2-tailed) obtained a significance value of 0.024 < 0.05 so that H_0was rejected and H_a accepted. So it can be concluded that the influence of the peer instruction flipped learning model on students' mathematical problem-solving ability is in the medium category.